The Influence of Content Marketing and Influencers on Online Buying Interest in Motorcycle Spare Parts at TikTok Shop - Muhamad Munawir; Ezhar Taqfhiran Calies; H Misbak; Tiara Muthiarsih (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of content marketing and influencers on generation Z's online buying interest in motorcycle spare parts products on the TikTok platform. Using a quantitative descriptive method with survey techniques, the study involved 200 respondents of generation Z TikTok users who had purchased motorcycle spare parts products through purposive sampling. Data was collected using an online questionnaire with a Likert scale and analyzed using SPSS. The results showed that all variables were valid and reliable with normally distributed data. Multiple regression analysis resulted in the equation Y = 8.837 + 0.220X1 + 0.515X2, showing content marketing (t = 5.632; sig = 0.000) and influencers (t = 7.148; sig = 0.000) have a significant positive effect on online purchase intention. The F test shows Fcount = 154.877> Ftable = 3.04 with a significance of 0.000, proving that both variables simultaneously have a significant effect. The coefficient of determination of 0.611 shows content marketing and influencers explain 61.1% of the variation in online purchase intention, with a strong correlation of content marketing (r = 0.714) and influencers (r = 0.741). The findings confirm digital marketing strategies through content marketing and influencer marketing are effective in increasing Generation Z's online purchase intention on motorcycle spare parts products on the TikTok platform.